The alterations of gut microbiota in mice with chronic pancreatitis - Han, Man-Man (Ann Transl Med, 2019)
BACKGROUND: The changes of intestinal microbiome are associated with inflammatory, metabolic, and malignant disorders, and there are no studies assessing the intestinal microbiota of mice with chronic pancreatitis (CP). Thus, we aim to investigate the variations in diversity, composition and function of intestinal microbiota in CP mice. METHODS: Sixteen male C57BL/6 mice were randomly selected, and divided into two groups, treated intraperitoneally with saline (normal control group, CT group) or ethanol + cerulein (experimental group, CP group) for 6 weeks. Body weight as measured in entire processes. Histopathological examination of CP index was conducted to verify the CP induction. Extracted DNA from colon samples was used for Illumina HiSeq sequencing of the bacterial V4 region of 16S rRNA gene and analyzed using Quantitative Insights Into Microbial Ecology (QIIME). Functional profiling of microbial communities was predicted with BugBase. RESULTS: Significant alterations of the gut microbiota were found in the CP mice compared to CT groups, as revealed by significant decrease in bacterial richness and diversity, declined the relative abundance of Lachnospiraceae_NK4A136, Ruminiclostridium and Roseburia, and increased the relative abundances of Bacteroides and Alloprevotella genera. Analysis of microbial community-level phenotypes revealed significant differences in nine phenotypes (aerobic, anaerobic, containing mobile elements, facultatively anaerobic, biofilm forming, gram-negative, gram-positive, potentially pathogenic, and stress tolerant) between CP group and CT group. CONCLUSIONS: This study indicated that mice with CP had a distinct microbiota profile.